2015
DOI: 10.1080/19392699.2015.1033097
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Occurrence and Promising Recovery Methods of Rare Earth Elements from Coal and Coal By-Products

Abstract: Previous research indicates that coal and coal by-products are a potential source of critical elements including rare earth elements (REE) with estimated amounts in the range of 50 million metric tons. Despite the proven presence of elevated REE concentrations, commercial extraction and recovery have not been realized. This article provides a review of the abundance, mode of occurrence, and recovery methods of rare earth elements in coal and coal by-products. The feasibility of using established REE extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(94 citation statements)
references
References 107 publications
3
90
0
1
Order By: Relevance
“…This is consistent with previous studies showing REE phosphate minerals in coals and coal ashes. 18,23,28,57,58 The stark contrast between YPO 4 -like points (e.g. App-FA3 Map 4) and those resembling the bulk ts (App-FA3 Map 6) highlights the importance of scale when considering Y speciation.…”
Section: Bulk and Micro-scale Yttrium Speciationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with previous studies showing REE phosphate minerals in coals and coal ashes. 18,23,28,57,58 The stark contrast between YPO 4 -like points (e.g. App-FA3 Map 4) and those resembling the bulk ts (App-FA3 Map 6) highlights the importance of scale when considering Y speciation.…”
Section: Bulk and Micro-scale Yttrium Speciationmentioning
confidence: 99%
“…western U.S.) coals. 7,[16][17][18] However, the mass of acid-extractable REE is oen similar for eastern and western U.S. coal ashes due to the high leachability of REE in Powder River Basin coal ashes. 7,19,20 Appalachian-and Illinois Basinderived ashes require more aggressive methods to decompose the aluminosilicate glasses (such as alkaline extractions) for effective leaching of the REE into solution.…”
Section: Introductionmentioning
confidence: 99%
“…The concern about the REE supply challengehas led to increasing interest and research in the recovery of REE from end-of-life products such as permanent REE magnets, nickel metalhydride batteries and lamp phosphors [5] and from secondarysourcessuch as coal and coal mining and combustion by-products [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The worldwide average total REY(lanthanides and yttrium) concentrations are 68.5 ppm and 404 ppm for coal and coal ash, respectively [7,8]. Recent studies showed that the beneficial recovery of REE from coal requires a minimum rare earth oxide (REO) concentrationof 800-900 ppm in the coal ash [6,[9][10][11]. Based on this datum, Zhang et al [6] further estimated the cut-off grade of REE in coal which is 115-130 ppm on the whole coal basis and 677-762 ppm on the ash basis.…”
Section: Introductionmentioning
confidence: 99%
“…The recovery of rare earth elements from coal, through the use of permeable reactive barrier material as evaluated in the present study, can be obtained through solvent extraction, electrowinning, magnetic and electrostatic separation, flotation or precipitation 72 . This aspect can be an opportunity that adds value to the PRB, which should be studied in the future.…”
Section: Resultsmentioning
confidence: 99%